2018
DOI: 10.1093/infdis/jiy059
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Anal Human Papillomavirus Infection in Human Immunodeficiency Virus–Positive Men Who Have Sex with Men

Abstract: Human papillomavirus 16 is ubiquitously frequent among human immunodeficiency virus -positive men having sex with men, and more strongly associated with high-grade anal lesions than other high-risk types, confirming it as a target for anal cancer prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 27 publications
8
31
1
1
Order By: Relevance
“…All individuals with an HSIL harbored an HR HPV infection with the exception of 1 HIV‐infected patient who was positive for possibly carcinogenic HPV‐53. These results are consistent with those reported in a recent French multicenter study of HIV‐infected MSM and in a cross‐sectional study of HIV‐infected men recruited in Taiwan …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…All individuals with an HSIL harbored an HR HPV infection with the exception of 1 HIV‐infected patient who was positive for possibly carcinogenic HPV‐53. These results are consistent with those reported in a recent French multicenter study of HIV‐infected MSM and in a cross‐sectional study of HIV‐infected men recruited in Taiwan …”
Section: Discussionsupporting
confidence: 92%
“…All individuals with an HSIL harbored an HR HPV infection with the exception of 1 HIV-infected patient who was positive for possibly carcinogenic HPV-53. These results are consistent with those reported in a recent French multicenter study of HIV-infected MSM 35 and in a cross-sectional study of HIV-infected men recruited in Taiwan. 36 We also found that the detection of HPV-16/18, the most prevalent genotypes in anal cancer, 37 increased with the severity of the cytological lesions in both study groups, and there was a peak in HSILs, which were HPV-16/18positive in 50% to 67% of the cases.…”
Section: Cancer Cytopathologysupporting
confidence: 92%
See 1 more Smart Citation
“…As chronic HPV infections in particular with multiple and high‐risk HPV represent a risk factor for AIN and anal carcinoma, subjects were clinically examined for signs of an HPV infection such as condylomata acuminata . Anal condyloma was significantly associated with abnormal screening results ( P = 0.045).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of HPV types, the most common types of high-risk genital HPV among HIV seropositive MSM in Taiwan were HPV16 (5.9%), HPV51 (7.9%) and HPV52 (7.2%) 20 . In Western countries, the most common types was HPV16, with a prevalence of 29.0% 27 . However, the prevalence of HPV52 was around 10% 7,27 .…”
Section: Discussionmentioning
confidence: 99%